An integrated production inventory model for perishable products with trade credit period and investment in preservation technology. (2016) - Tayal, Shilpy; Singh, S.R.; Sharma, Rajendra
In this paper we develop an integrated production-distribution model for deteriorating items in a two-echelon supply chain. The objective of this study is to develop an integrated inventory policy when the retailer invests on the preservation technology to reduce the product rate of deterioration and to investigate the model under conditions of permissible delay in payment and allowable shortages. This paper incorporates the concept of a credit period and develops a new inventory model to reflect real-life situations. Exact cost functions for the supplier, the buyer and the entire supply chain are developed. We outline a procedure for determining the optimal supply chain decisions with the objective of minimising the total system cost. Our approach is illustrated through a numerical example. Sensitivity analysis is also presented to illustrate this model.